Trace Molybdenum determination in drinking waters by USN-ICP-OES after solid phase extraction on Ethyl Vinyl Acetate turnings-packed minicolumn - Escudero, Luis Ariel (2008)
This study presents the development of a novel on-line preconcentration method for inorganic molybdenum by flow injection solid-phase extraction with detection by inductively coupled plasma optical emission spectrometry and ultrasonic nebulization (SPE-USN-ICP-OES). This method employs a minicolumn filled with ethyl vinyl acetate turnings as the adsorbent material. This system was applied to the on-line preconcentration and determination of molybdenum in water samples with good selectivity and reproducibility; molybdenum was retained on the minicolumn without further complexation. The time required for the preconcentration of a 20-mL sample, injection/data acquisition, and conditioning was about 5.0 minutes, resulting in a sample throughput of 12 samples per hour. A 300-fold total enhancement factor for this sample volume was obtained with respect to the molybdenum determination by ICP-OES without preconcentration. The precision for six replicate measurements of a solution containing 20 µg L-1 Mo was 3.5% relative standard deviation, calculated at peak height. The limit of detection (3σ) was 0.04 µg L-1. This method was successfully applied to trace molybdenum determination in drinking water samples and in a certified reference material (Metals in Natural Waters, NIST CRM 1643e).